The examination of the Tofā Māmāo cultural concept and repositioning it as a theoretical approach to guide Pacific research - Aliitasi Su’a-Tavila; James Mbinta (Kōtuitui)
While the emergence of Pacific scholars has contributed to the development of Pacific methodologies, they have not fully addressed the broader academic context in New Zealand. Appreciating the importance of diverse cultural values and beliefs among Pacific peoples, doing research with them must be honoured and acknowledged for its uniqueness. The Samoan cultural concept named Tofā Māmāo (in-depth knowledge) is a potential theoretical approach to guide Pacific research. This study explored Tofā Māmāo from the perspective of paramount chiefs and its theoretical position within academia. The talanoa (dialogue) approach was employed during the one-on-one interviews to collect the data. The findings revealed that the Tofā Māmāo is defined metaphorically as a Pearl of Wisdom and a principal philosophical element in the fa'a-Samoa (Samoan culture). Its principles are suitable for Pacific research and enrich the whole process. It symbolises the ability to unlock an archive of knowledge that has existed for generations. It defines truth through oral traditions which justifies its positioning when doing research. While Pacific metaphors and proverbs are elements of interpreting the meaning of the Pacific people's worldview, the significance of the Tofā Māmāo has a primary potential to inform the theoretical stance of the research.